Synthesis of C3-symmetric star-shaped molecules containing α-amino acids and dipeptides via Negishi coupling as a key step - Kotha, Sambasivarao; Todeti, Saidulu (Beilstein Journal of Organic Chemistry, 2019)
We demonstrate a new synthetic strategy toward star-shaped C3-symmetric molecules containing α-amino acid (AAA) derivatives and dipeptides. In this regard, trimerization and Negishi cross-coupling reactions are used as the key steps starting from readily available 4’-iodoacetophenone and L-serine. These C3-symmetric molecules containing AAA moieties are useful to design new ligands suitable for asymmetric synthesis and peptide dendrimers.
Keywords: amino acids; cyclotrimerization; Negishi coupling; peptide